Machado de assis's epilepsy - Carlos A. M. Guerreiro (Arquivos de Neuro-Psiquiatria)
Machado de Assis (1839-1908) is considered the most important Brazilian writer and a great universal literary figure. Little is know about his medical, personal and family history. He hid his «disease» as much as possible. Machado referred to «strange things» having happened to him in his childhood. He described seizures as «nervous phenomena», «absenses», «my illness». Laet observed a seizure and described it as: «... when Machado approached us and spoke to me in disconnected words. I looked at him in surprise and found his features altered. Knowing that from time to time he had nervous problems,... and only permitted Machado take the Laranjeiras Street car, when I saw that he was completely well». A photographically documented seizure is shown. Alencar wrote, «The preoccupation with health was frequent: either he was having the consequences of a fit or was foreboding one». It is clear that Machado presented localized symptomatic epilepsy with complex partial seizures secondarily generalized of unknown etiology. The seizures which began in infancy or childhood had remission in adolescence and then recurred in his thirties and became more frequent in his later years. His depression got markedly worse with age. In our opinion, the greatest consequence of Machado's epilepsy, was his psychological suffering due to the prejudice of the times. Despite this Machado showed all his genius, which is still actual and universal.